The Main Approaches to The Definition of Food Security & Agricultural Chemistry: History, Modernity, Health Issues: Life Sciences-Health - Belyaeva, Galina S.; Krikun, Elena V.; Mantul, Grigory A.; Saidov, Zaurbek A. (International Journal of Life Science and Pharma Research, 2022)
The definition of food security is the physical, social and economic access of all people at all times to sufficient and healthy food so that their food needs and food preferences are met for a healthy and active life. This current article aims to analyze the issues regarding the main approaches to the definition of food security & agricultural chemistry in retrospect, as well as in the current state, health issues, and development perspective. Regarding the importance of food security in health, we can mention: ending hunger, achieving food security and better nutrition; everyone's access to safe, nutritious and sufficient food throughout the year, ending various forms of malnutrition. Increasing agricultural productivity and access to production resources, and creating sustainable food production systems. To that end, multiple general scientific techniques and knowledge methods (deduction, induction, formal-logical approaches, synthesis, analysis, and system-structural are utilized. Considering the results, policymakers and regulators of development programs have considered the following in determining and regulating the main approaches of the agricultural sector: ensuring food security, maintaining vanilla production capacity to be self-sufficient in basic products, supporting the agricultural sector, and protecting basic resources and improving productivity. It is established that the legal definition of food security & agricultural chemistry exists only at the subordinate level, in a document of a doctrinal nature, in the Russian Federation. It is concluded that there is no federal legislation in our country specifically dedicated to the legal regulation of food security. The formation stages of the concept of food security described in the paper demonstrate the evolution of the international concept of food security & agricultural chemistry and the problems of its current state, which shall be taken into account by the domestic legislator when developing national legislation.